2000
DOI: 10.1046/j.1432-1327.2000.01467.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxic lactonic lipopeptide from food poisoning isolates of Bacillus licheniformis

Abstract: Toxins from three Bacillus licheniformis strains connected to a fatal food poisoning were isolated and their structures elucidated. Toxins were purified from methanol extracts of the B. licheniformis biomass using boar sperm cells as the toxicity indicator. The HPLC purified toxins showed protonated masses m/z 1007, 1021 and 1035 in MALDI-TOF-MS. The toxins isolated from the strains of different origins contained the same three components of which and each had a same amino-acid residues l-Gln, l-Leu, d-Leu, l-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…These differences among the cytotoxicity assays may suggest intracellular effects due to exposure to antimicrobial peptides before any permanent cell membrane damage occurred. In this regard, the antibiotics nisin, subtilin, Pep5 and epidermin have secondary modes of action in addition to their well‐stablished bacteriolytic action (McAuliffe et al, 2001). The cytotoxicity of nisin, pediocin and colicins was tested with Vero cells using a Trypan Blue staining viability assay (Murinda et al, 2003), but the EC 50 values showed little correlation with the values reported here.…”
Section: Discussionmentioning
confidence: 99%
“…These differences among the cytotoxicity assays may suggest intracellular effects due to exposure to antimicrobial peptides before any permanent cell membrane damage occurred. In this regard, the antibiotics nisin, subtilin, Pep5 and epidermin have secondary modes of action in addition to their well‐stablished bacteriolytic action (McAuliffe et al, 2001). The cytotoxicity of nisin, pediocin and colicins was tested with Vero cells using a Trypan Blue staining viability assay (Murinda et al, 2003), but the EC 50 values showed little correlation with the values reported here.…”
Section: Discussionmentioning
confidence: 99%
“…B. licheniformis has been reported in cases of food‐borne diarrhoeal illness, toxin production and infant mortality [164]. B. subtilis has been implicated in food‐borne illnesses, with vomiting being the most common symptom [165].…”
Section: The Safety Of Bacillus Productsmentioning
confidence: 99%
“…Several in vitro studies have indicated a strong correlation between surfactin and lichenysin and their toxicity towards different mammalian cells (Mikkola et al . ; Nieminen et al . ; Apetroaie‐Constantin et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Mikkola et al . ), a small cyclic lipopeptide (CLP) structurally very similar to surfactin (Arima et al . ) and pumilacidin (Naruse et al .…”
Section: Introductionmentioning
confidence: 99%